Kerja Sama Indonesia dan Inggris dalam Upaya Meningkatkan Kapabilitas Keamanan Siber - Nawwar Shafwan Mudlaffar Aksah; Imam Fadhil Nugraha (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This paper analyzes bilateral cooperation between Indonesia and the UK in the field of cybersecurity. Cyber ​​threats are increasingly complex and require a collaborative approach that cannot be addressed independently by each country. Indonesia as a developing economy with high internet faces significant cyber dynamics, while the UK has technological advantages and mature cybersecurity experience. Using a descriptive qualitative analysis approach, this paper examines bilateral agreements, data, and related literature to understand the dynamics of this cooperation. Therefore, this paper shows that this cooperation is based on the strategic interests of both countries in maintaining regional and global security stability, as well as the rampant cyber threats in the current digital era. Indonesia chose the UK as its main partner because of its technological advantages in AI and digital innovation. This cooperation is implemented through personnel exchange mechanisms, technical training, and research and development collaboration.